2006
DOI: 10.1007/s11116-006-9108-2
|View full text |Cite
|
Sign up to set email alerts
|

Land use-transportation scenario planning: promise and reality

Abstract: Land use-transportation scenario planning has become increasingly common in regional and sub-regional planning processes. The technique promises to provide citizens with opportunities to engage in constructive dialogue about the future of their communities, and to serve as a basis for assertive action to direct the course of that future. This study reviews 80 scenario planning projects from more than 50 U.S. metropolitan areas. The analysis reveals important gaps in the practice of scenario planning—particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 5 publications
0
68
0
2
Order By: Relevance
“…U projektu ÖROK-a (n. d.) pak izrađeni su scenariji prostornog razvoja Austrije. Prema Bartholomew (2007), mnoga metropolitanska područja u SAD-u u posljednja dva desetljeća primjenjuju tehnike opisivanja budućnosti svojih zajednica; često jedan od oblika scenarijskog planiranja za kvantitativno vrednovanje nekoliko inačica razvoja, i analizu njihovih učinaka na različite indikatore (od cijene stanovanja do kvalitete vode). Özkaynak (2008) pokazala je na primjeru grada Yalova u Turskoj kako izrada i analiza scenarija mogu pomoći urbanom planiranju i upravljanju manjim do srednje velikim gradovima.…”
Section: Scenario Methods In Spatial Research and Planningunclassified
See 1 more Smart Citation
“…U projektu ÖROK-a (n. d.) pak izrađeni su scenariji prostornog razvoja Austrije. Prema Bartholomew (2007), mnoga metropolitanska područja u SAD-u u posljednja dva desetljeća primjenjuju tehnike opisivanja budućnosti svojih zajednica; često jedan od oblika scenarijskog planiranja za kvantitativno vrednovanje nekoliko inačica razvoja, i analizu njihovih učinaka na različite indikatore (od cijene stanovanja do kvalitete vode). Özkaynak (2008) pokazala je na primjeru grada Yalova u Turskoj kako izrada i analiza scenarija mogu pomoći urbanom planiranju i upravljanju manjim do srednje velikim gradovima.…”
Section: Scenario Methods In Spatial Research and Planningunclassified
“…In the frame of ÖROK (n. d.) scenarios of spatial development of Austria were constructed. According to Bartholomew (2007), many metropolitan areas in the United States have engaged in a form of visioning in the last two decades to describe a future for their communities; often as a form of scenario planning to evaluate quantitatively several alternative development patterns and analyse their impacts along different indices (ranging from the affordability of housing to water quality). Using the example of Yalova in Turkey, Özkaynak (2008) showed how scenario building and analysis can contribute to small and medium-sized city planning and governance.…”
Section: Scenario Methods In Spatial Research and Planningmentioning
confidence: 99%
“…Still, the impetus to move toward greater integration and coordination on transportation and land use policies has been reflected in metropolitan planning practice in the decades since ISTEA, particularly in the rise of land use-transportation scenario analysis. Research by Bartholomew (2007) and Bartholomew and Ewing (2009 identified more than 100 examples of regional-scale scenario analyses utilizing some measure of land use-transportation policy integration and coordination. The seeming ubiquity of the approach led Ewing to opine in 2007 that the approach had, in the space of a decade and a half, gone from the fringes of planning practice to being a staple (Ewing, 2007).…”
Section: Mpo Roles In Transportation-land Use Integrationmentioning
confidence: 99%
“…Nor has existing research provided empirical methodologies founded on collaboration theory. Without more research on such second-order process-related effects, we cannot know whether, and to what extent, this -organizationallearning‖ aspect of scenario planning holds true, especially in the land use-transportation planning arena, where some forms of the technique have recently surged in popularity [43].…”
Section: Literature Evaluating Scenario Planningmentioning
confidence: 99%